Pendugaan Hazard Rate Letusan Gunung Sinabung dengan Metode Single Decrement Pendekatan Likelihood - Gurusinga, Ditha Aulia; Lubis, Riri Syafitri; Cipta, Hendra (Universitas Multi Data Palembang, 2024)
Abstract The eruption on Mount Sinabung made North Sumatera the province with the highest frequency of volcanic eruptions and the highest prevalence of deaths in Indonesia. As a consideration for reducing the risk of volcanic eruptions, a risk map was created through mathematical model calculations containing hazard rate values ​​based on the number of Mount Sinabung eruptions which became variables in the regression model for estimating the hazard rate of Mount Sinabung eruptions using the single decrement likelihood approach method. The research results show that the hazard rate value for the eruption of Mount Sinabung in 2020 has the largest value, namely 0.20765. The best and most feasible model after calculating the smallest Mean Squared Error (MSE), namely 0.000616 from the results of the hazard rate which has been transformed into the box cox, is the quadratic model. Through this model, it is assumed that the estimated hazard rate values of Mount Sinabung eruptions ​​in 2021, 2022 and 2023 will increase respectively.